Successful (neo)adjuvant BRAF-targeted therapy in a patient with locally advanced BRAF V600E mutant melanoma. Issue 2 (April 2015) - Seremet, Teofila; Lienard, Danielle; Suppa, Mariano; Trepant, Anne-Laure; Rorive, Sandrine; Woff, Erwin; Cuylits, Nicolas; Jansen, Yanina; Schreuer, Max; del Marmol, Véronique; Neyns, Bart
Abstract : The treatment of locally advanced metastasized melanoma is challenging because there is no level 1 evidence to guide clinical decision-making. Moreover, the treatment options available fail to improve overall survival and are associated with considerable morbidity. Here, we show that systemic treatment with BRAF inhibitor vemurafenib substituted by dual BRAF/MEK inhibition (dabrafenib and trametinib) before surgery can offer the potential to cure the initially difficult or inoperable melanoma. A 62-year-old woman was diagnosed with an AJCC stage IIIB melanoma harboring the BRAF V600E mutation after a complete initial evaluation. Clinically, the patient presented a large primary lesion that was surrounded by ∼25 secondary epidermotropic lesions both satellite and 'in transit' with a diameter between 1 and 6 mm. Following multidisciplinary consultation, the patient was started on 960 mg twice-daily vemurafenib, which was stopped and resumed at 720 mg twice daily, and finally substituted with the combination dabrafenib and trametinib to reduce the persistent side effects. Successive clinical examinations had shown a progressive reduction in the thickness of the melanoma lesions. After about 5 months of therapy, surgery was performed and the histopathological analysis showed an almost complete regression of tumor cells. The treatment with dabrafenib/trametinib was continued only 3 months after surgery and stopped at the patient's request. The patient currently remains in complete remission at 8 months after surgery. The case presented here supports the use of neoadjuvant treatment with BRAF inhibitors in advanced 'in transit' melanoma.